Finding Mountains with Music: Growth and Spiritual Transcendence in a U.S. Prison - Rhodd, Anthony R.; Cohen, Mary L. (2022)
Resulting in pervasive feelings of despair, the culture of incarceration in the U.S. relies on punitive correctional strategies such as solitary confinement to control the behavior of incarcerated individuals. Inevitably, correctional culture which focuses primarily on punishment is dysfunctional, rife with gang violence, drug use, suicide, and violence perpetuated by and against staff. Our dialogic essay is voiced by (a) a currently incarcerated, Native American person who has survived solitary confinement and the spiritual drain of castigating correctional culture; and (b) a music educator who founded a prison choir for both non-incarcerated and incarcerated individuals in an effort to erode and transform some of the revengeful structures of US incarceration. We draw from Indigenous educator, language specialist, and member of the Lil’wat First Nation, Dr. Lorna Williams’ research on Indigenous Knowledge in our efforts to understand the relationships among group singing, spirituality, and our experiences in the Oakdale prison choir. Our dialogue charts a search for spiritual healing in the unsympathetic atmosphere of prison and offers an experience-based account of ways in which group singing can function as a medium of spiritual healing and growth in environments of conflict.
Keywords: collaborative autoethnography; Conflict; Ritual; group singing; Indigenous Knowledge; Native American; Solitary Confinement; Incarceration; prison choir